Entrepreneurial Risk: Essence and Classification Depending on the Losses Borne by the Entrepreneur - Iryna Abernikhina (Облік і фінанси, 2023)
In conditions of high competition and variability of economic conditions, timely insurance of business risks can help the enterprise to preserve its financial resources and ensure stability and security in the market. The article aims to systematize business risks by groups of losses and generalize and characterize the types of insurance policies that can be useful to the enterprise due to their manifestations. It was found that entrepreneurial risk in economic activity is a generalizing term for a group of risks that arise at various stages of the capital cycle as a result of the actions of the enterprise itself, competitors, counterparties, changes in the market situation, technological failures and other internal and external factors. Types of business risks are systematized. Four main groups of enterprise losses due to business risks were identified, with the selection of types of insurance policies that can be useful for enterprises in case of corresponding losses. Different conditions for insurance against cyber threats and liability for environmental damage in Ukraine were disclosed under four main costs depending on the type of damage subject to compensation. The results of the study show that business risk is a complex category that covers various aspects of business activity, protection against which occurs mainly within the scope of property insurance and liability insurance, but at the same time can go beyond these fields of insurance, if it is determined by the needs of business activity Business risk includes financial risks, such as market instability, changes in the economic environment, exchange rate fluctuations, rising costs, insufficient financial resources. It also covers operational risks related to business management, including supply chain issues, staffing issues, technology failures, legal conflicts, and more.